2004
DOI: 10.1016/s0032-3861(04)00442-2
|View full text |Cite
|
Sign up to set email alerts
|

Cure reactions in the blend of cyanate ester with maleimide

Abstract: Cure reactions of a bismaleimide (4,4 0 -bismaleimidodiphenylmethane, BMI) associated with a liquid aromatic dicyanate ester (1,1 0 -bis(4-cyanatophenyl)ethane, BEDCy) and with a powder type aromatic dicyanate ester (bisphenol A dicyanate, BADCy) were investigated by in situ FTIR and DSC dynamic scanning. In non-catalyzed blend systems, co-reactions between dicyanate ester and bismaleimide always occur, and hence the formation of pyrimidine and/or pyridine structures take place. Pyrimidine structures always pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 11 publications
(21 reference statements)
2
30
0
Order By: Relevance
“…However, the cured resin is extremely brittle because of its high cross-link density. Several efforts have been focused on the toughening modification of BMI resin [15][16][17]. One of the most desirable methods for improvement is the copolymerization of BMI with allyl compounds such as O,O 0 -diallyl bisphenol A (DBA), O,O 0 -diallyl bispihenol A ether, allylated novolac, and allylated xylok [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…However, the cured resin is extremely brittle because of its high cross-link density. Several efforts have been focused on the toughening modification of BMI resin [15][16][17]. One of the most desirable methods for improvement is the copolymerization of BMI with allyl compounds such as O,O 0 -diallyl bisphenol A (DBA), O,O 0 -diallyl bispihenol A ether, allylated novolac, and allylated xylok [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The two absorptions weakened as the temperature raised and finally disappeared after BT60 was cured at 2608C for 2 h, while the absorption at 1560 cm 21 assigned to the absorption of triazine appeared and strengthened. 30 It suggested that BADCy self-polymerized and gave a triazine structure (I). Absorption at 690 cm 21 belonged to carbon-carbon double bond of maleimide 31 weakened as the cure temperature rose, which implied that the homopolymerization of DOPO-BMI (II) or the co-curing of DOPO-BMI and BADCy occurred at high temperatures.…”
Section: Processability and Cure Behavior Of Dopo-bmi-based Bt Resinsmentioning
confidence: 99%
“…The approaches include addition of high-thermoplastic tougheners [12][13][14], rubber inclusions [15][16][17][18], inorganic or organic fillers [19][20][21][22][23], thermosetting resins [24,25], and flexible molecules [26][27][28]. However, these methods are largely ineffective in restoring strength to cracked or damaged material.…”
Section: Introductionmentioning
confidence: 99%